Modelling the crop variety demand of semi-subsistence households: Bananas in Uganda - Edmeades, Svetlana; Phaneuf, Daniel J.; Smale, Melinda; Renkow, Mitch (Wiley, 2008)
We propose an approach to model the derived demand for crop varieties among semi‐subsistence farmers in a developing economy, and apply it to smallholder banana producers in Uganda. We model variety planting decisions as being composed of an extensive margin decision to grow a subset of locally available varieties (variety choice); and an intensive margin decision about the scale or extent of variety cultivation per farm (variety demand). We estimate variety demand equations using a more complete representation of the choice set upon which observed planting decisions are made. Computed elasticities of variety demand with respect to variety attributes indicate that the relative importance of consumption and production attributes varies by location and proximity to markets, from which we draw implications for the social and economic impact of crop improvement. The approach that we propose has broad appeal for analysing adoption decisions for modern or traditional varieties of both major and minor crops in developing countries.